Twisted sister species of pygmy angelfishes: Discordance between taxonomy, coloration, and phylogenetics - Di Battista, Joseph; Waldrop, E.; Bowen, B.; Schultz, J.; Gaither, M.; Pyle, R.; Rocha, L. (Springer Verlag, 2012)
The delineation of reef fish species by coloration is problematic, particularly for the pygmy angelfishes (genus Centropyge), whose vivid colors are sometimes the only characters available for taxonomic classification. The Lemonpeel Angelfish (Centropyge flavissima) has Pacific and Indian Ocean forms separated by approximately 3,000 km and slight differences in coloration. These disjunct populations hybridize with Eibl's Angelfish (Centropyge eibli) in the eastern Indian Ocean and the Pearl-Scaled Angelfish (Centropyge vrolikii) in the western Pacific. To resolve the evolutionary history of these species and color morphs, we employed mitochondrial DNA (mtDNA) cytochrome b and three nuclear introns (TMO, RAG2, and S7). Phylogenetic analyses reveal three deep mtDNA lineages (d = 7. 0-8. 3 %) that conform not to species designation or color morph but to geographic region: (1) most Pacific C. flavissima plus C. vrolikii, (2) C. flavissima from the Society Islands in French Polynesia, and (3) Indian Ocean C. flavissima plus C. eibli. In contrast, the nuclear introns each show a cluster of closely related alleles, with frequency differences between the three geographic groups. Hence, the mtDNA phylogeny reveals a period of isolation (ca. 3. 5-4. 2 million years) typical of congeneric species, whereas the within-lineage mtDNA F ST values and the nuclear DNA data reveal recent or ongoing gene flow between species. We conclude that an ancient divergence of C. flavissima, recorded in the non-recombining mtDNA, was subsequently swamped by introgression and hybridization in two of the three regions, with only the Society Islands retaining the original C. flavissima haplotypes among our sample locations. Alternatively, the yellow color pattern of C. flavissima may have appeared independently in the central Pacific Ocean and eastern Indian Ocean. Regardless of how the pattern arose, C. flavissima seems to be retaining species identity where it interbreeds with C. vrolikii and C. eibli, and sexual or natural selection may help to maintain color differences despite apparent gene flow. © 2012 Springer-Verlag.